UPAYA GURU DALAM IMPLEMENTASI PENDEKATAN SAINTIFIK PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SISWA KELAS XIIDI SMA NEGERI 1 TELUK KUANTAN - Muhammad Rizki Lazuardi; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
The problem in this research is how is the teacher's effort in implementing a scientific approach in the field of study of Islamic Religious Education and Characteristics of Grade XII students in SMA Negeri 1 Teluk Kuantan? As subjects in this study were 1 Islamic Religious Education teacher who taught grade XII students at SMA Negeri 1 Teluk Kuantan and all XII grade students totaling 268 people divided into 8 groups, 5 groups of MIPA majors and 3 classes of social studies majors and as subjects is the effort of the teacher in implementing the Scientific approach in the field of study of Islamic Religious Education and Characteristics of Grade XII students at SMA Negeri 1 Teluk Kuantan. Based on the results of data collection by means of observation, interviews and documentation, the results of data processing can be concluded that: the efforts of teachers The implementation of a scientific approach to the learning of Islamic Religious Education and Characteristics of Class XII students in SMA Negeri 1 Teluk Kuantan has been carried out properly and correctly. These include: When students are less daring to ask or do not ask questions related to the material to the teacher, the teacher tries to lure students with light questions and with explanations that provoke students to ask, when students are unable to reason based on observations and experiments, the teacher gives examples that make students more capable and try their best to make sense of the material about the doomsday. When students have not been able to design experiments to test these hypotheses, the teacher continues to provide other examples that are commensurate and when students lack understanding of the activities to try, the teacher gives a need for example.